Medication overuse headache and substance use disorder: A comparison based on basic research and neuroimaging - Li, Chenhao; Dai, Wei; Miao, Shuai; Xie, Wei; Yu, Shengyuan (Frontiers in Neurology, 2023)
It has not been determined whether Medication overuse headache （MOH） is a combination of primary headache and substance addiction or an independent disease. To further analyze the causes of MOH, we decided to compare MOH with substance use disorders in terms of the brain regions involved, and then draw more targeted conclusions. In this review, we selected alcohol use disorder (AUD) as the representative of substance use disorder diseases for the main analysis and compared them from two aspects of neuroimaging and basic research. By comparing MOH with AUD, we found that in neuroimaging, there were many overlaps in the reward circuit, but the extensive cerebral cortex damage of AUD was more serious than that of MOH. This change was considered to be the sensitivity of the cortex structure to alcohol. In future research, we can focus on the central amygdala （CeA）, prefrontal cortex （PFC）,orbital-frontal cortex （OFC）, hippocampus, and other brain regions to intervene in these key structures, which may have unexpected effects on MOH addiction and headache symptoms at the same time.